Exploring Interactions Between NCAA Division I Athletic Directors and University Presidents - Carrie W. LeCrom; Angela N. Pratt (University of Kansas Libraries, 2016)
The landscape of college athletics is rapidly changing, due to issues like conference realignment, deregulation, academic integrity, and presidential control. As member institutions work toward a shared vision and future, the role of the athletic director (AD) continues to evolve and change. Given these changes and the increase in presidential control over National Collegiate Athletic Association (NCAA) issues, this study explored relationship dynamics between ADs and presidents on university campuses from the perspectives of ADs. Research questions addressed what these interactions look like in developing a relationship between AD and president, how to foster positive interactions, and how to maintain them. Interviewing 12 ADs from a variety of Division I institution types, four major themes emerged: trust and communication, alignment, respect for expertise, and formal and informal relationships. In addition, the ADs interviewed talked at length about the relationship with presidents on their own campus, as well as at the national level, where there seemed to be a lower sense of control. The authors suggest strategies for working toward these four themes as well as implications for future research in this area.